Authoritarian Modernization in Indonesia's Early Independence Period The Foundation of the New Order State (1950-1965) - Fakih, Farabi (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2020)
In Authoritarian Modernization in Indonesia's Early Independence Period, Farabi Fakih offers a historical analysis of the foundational years leading to Indonesia's New Order state (1966-1998) during the early independence period. The study looks into the structural and ideological state formation during the so-called Liberal Democracy (1950-1957) and Sukarno's Guided Democracy (1957-1965). In particular, it analyses how the international technical aid network and the dominant managerialist ideology of the period legitimized a new managerial elite. The book discusses the development of managerial education in the civil and military sectors in Indonesia. The study gives a strongly backed argument that Sukarno's constitutional reform during the Guided Democracy period inadvertently provided a strong managerial blueprint for the New Order developmentalist state. Readership: All those interested in the political history of Indonesia, the history of the developmental state and the history of managerial ideology.